Tradisi Maulid Nabi Dalam Masyarakat Sasak - Zaenuddin Mansyur (Universitas Islam Negeri Mataram, 2005)
Every community has one or more celebration day that it traditionally celebrates in certain way. One of Muslims’ most impressive celebration day is the birthday of Muhammad (mawlid), the last massenger of God. To Muslims Muhammad is considered the gloriest and the leader of all massenger sent by Allah to human being. He preached Islam and got success in his mission in a relatively short period, 23 years. His 23-year mission period was considered the turning point in the history of Muslims (Arabs) civilization from the age of pagan ignorance (jâhiliyah) toward a new, enlightened, and civilized era. His very hard strugle and great succesful-end mission took special place in the heart of Muslims all over the world and inspired them to do their best in commemorating his piety and heroic life. All he had done dan gained in preaching Islam rose great proudness and admiration to the Muslim communities all over the world, so that they are always very eager to commemorate his birthday in various ways of celebration in accordance with their own culture and traditions. The Sasak community in Lombok island traditionally named celebration of Muhammad birthday mulud—derivated from Arabic word mawlid—and held constantly every year. The historical, philosophical, and sociological aspects of Sasak tradition simutanously colored mulud celebration. It has lasted for a long time, and the community has endured it through the process of tradition and regeneration but some changes have been in one or more aspects of the commemoration rituals.